FRI0330 Fatigue and depression in patients with behcet's disease. (15th June 2017) - Silva, JL; Santos-Faria, D; Sousa-Neves, J; Rodrigues, J; Costa, J; Afonso, C; Peixoto, D
Abstract : Background: Behcet's disease (BD) is a systemic vasculitis of unknown etiology defined by a classic triad consisting of aphtous ulcers of the mouth and genital and uveitis. In addition to these, BD may involve cardiovascular, pulmonar, neurological, articular and gastrointestinal manifestations. Fatigue, anxiety and depression are important problems in chronic inflammatory diseases. There are few studies on fatigue in BD patients. Ilhan et al. 1 reported more fatigue in BD patients than in healthy controls. Objectives: The objective of this study was to investigate fatigue and depression in patients with BD and to examine the relationship between these symptoms and disease activity and gender. Methods: Forty four patients with BD and thirty nine healthy controls (HC) were included in this study. Age, gender, disease duration and clinical involvements were recorded. All subjects completed the FACIT Fatigue Scale (FACIT-F), Short Form-36 (SF-36), Hospital Anxiety and Depression Scale (HADS) and Health Assessment Questionnaire (HAQ). Disease activity among BD patients was assessed using the Birmingham Vasculitis Activity Score (BVAS). Results: The mean age was 40.0 years for BD patients and 38.7 for HC. 77% of BD patients were women. The mean disease duration for BD patients was 6.1 years. All patients had oral ulcers and genital ulceration; 20 had pseudofolliculitis; 9 had uveitis, 9 had erythema nodosum, 12 had articular involvement, 5 patients had vascular involvement, 4 had pathergia, 1 had orchitis and one had gastrointestinal involvement. Thirty two BD patients were taking medication, including colchicine or DMARDs or their combinations. Seventeen patients had inactive disease and twenty seven had BVAS ≥1. As shown in Table 1, both the HADS-depression (HADS-D) (4.7 vs 2.5) and HADS-anxiety (HADS-A) (8.3 vs 5.7) scores were elevated in BD patients compared to healthy controls. FACIT-F was higher in healthy controls in comparison with BD group (44.1 vs 36.6), revealing lower levels of fatigue. There were no differences between gender on these scores. There were no significant differences in FACIT-F, HADS-A and HADS-D scores with the disease activity (P=0.952, P=0.391 and P=0.286, respectively). FACIT-F had a negative correlation with HAQ and HADS and a positive correlation with the different components of SF-36 and age. FACIT-F score was not correlated with disease duration (Table 2). Conclusions: In our study, fatigue and increased levels of anxiety and depression were more common in BD patients. Contrary to the study of Ilhan et al 1, we found that fatigue was not higher in patients with active disease. Similarly, there were no correlation between the assessed scores and gender. In spite of these results, the authors believe that controlling the symptoms may improve the quality of life in BD patients. References: Ilhan et al. Fatigue in patients with Behcet's syndrome: relationship with quality of life, depression, anxiety, diability and disease activity. International Journal of Rheumatic Diseases. 2016. Disclosure of Interest: None declared